Sistem Informasi Penyaluran Bantuan langsung Tunai (BLT) Dana Desa pada Kecamatan Alu Berbasis WEB - Harlin Harlin; Basri Basri; Sapriadi Sapriadi (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The distribution of Village Fund Direct Cash Assistance (BLT) is a government program aimed at alleviating the economic burden on affected communities. However, the data collection, verification, distribution, and reporting processes are still largely manual, potentially leading to data errors, duplication, and distribution delays. This study aims to design and implement a web-based BLT Village Fund information system that can simplify recipient data management, monitor distribution, and generate accurate reports. The methods used include database design, module implementation for sub-district administrators, village operators, treasurers, and village officials, and system testing using the Black Box method to evaluate functionality. The system is equipped with features for managing recipient data, verifying eligibility, sending data to the treasurer, inputting proof of transfer, uploading proof of distribution, recapitulating distribution, and printing reports. The test results show that all modules run according to specifications, are able to handle various input conditions, and produce accurate output. Field trials show that the system is easy to use, improves administrative efficiency, accelerates the distribution process, and supports transparency and accountability. In conclusion, the Village Fund Direct Cash Assistance (BLT) information system is effective as a tool for data management and aid distribution, minimizing errors, and supporting the smooth operation of the BLT program at the village level.